#TITLE_ALTERNATIVE# - ADYAWIBAWA SOEMANTRI (NIM:10208106), ERICH
Johnson & Johson, Merck & Co. Inc. and Pfizer Inc. are indeed three pharmaceutical company that highly attractive to the investors. To use time series to predict future prices movement, one must first analyze related historical time series. Fractional Brownian motion model,that connects the concept of Hurst exponent and fractal dimension, is the generalization of Brownian motion model, the model that already widely known dan used before. In this reseach, Hurst exponent and fractal dimension theory are being utilized to reveal and describe some of the characteristics of the time series especially for the predictibility and volatility aspect, furthermore a basic method, the cross correlation coefficient used for quantify the togetherness of the time-sync time series price movements. The result of the conducted reseach shows that the three pharmaceutical companies time series arenÃ‚Â’t actually an ideal realization of the the fractional Brownian motion model but despite of that in general the theoretical concepts that are used for the analysis still able revealing the characters of the three pharmaceutical companies time series.